Povyšenie effektivnosti trenirovocnogo processa tjaželoatletov na osnove biomechaniceskogo kontrolja tekušcej i etalonnoj traektorii štangi - Azeev, A. A.; Azeev, A. E.; Mikhaylenko, E. N.; Zavyalov, A. I.; Zhiganova, L. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
Objective of the study - to develop methods and technical means for recording, analysis and adjustment of the exercise biomechanics. The research is based on theoretical and experimental methods: comparative analysis, system approach, mathematical modelling and theory of experiment planning. It is shown that the research findings will demonstrate the efficiency of applying technical means with feedback, which allow setting a right stereotype of movement basing on the prompt information analysis on the movement capabilities of a sportsman. We have developed a complex of exercises with a system for recording, analysis and adjustment of the exercise biomechanics and the common centre of mass of the biomechanical system. A series of preliminary experiments was performed.